SMALL FARMERS, THEIR POSITION AND SUPPORT WITHIN THE CAP – CASE OF SLOVAKIA - Ľubica RUMANOVSKÁ; Jarmila LAZÍKOVÁ; Ivan TAKÁČ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The small farmers are an important element of sustainable agricultural production, multifunctional agriculture and rural development. It is the predominant mode of agricultural production in the world. Despite its predominance in the agricultural structure, small farming encounters several difficulties. Therefore, it is hard to imagine functioning of small farms without subsidies for production, especially direct area payments. The aim of the paper is to identify the development trend of small farmers in Slovakia and to point out their needs in the Slovak agricultural business environment. Based on the results we can expect a further increasing trend of number of small farmers in Slovakia. Therefore, we need to take into consideration their support and elimination of barriers in the Slovak environment, e.g. to improvement the access to the land, support of the business of the beginning farmers, improvement the possibilities to use the project support, improvement the access to the credits and improvement the access to the non-project measures. The adopted measures should be prepared carefully with the aim to eliminate the misuse the financial effect providing to support of agricultural business.